Adsorption of cadmium ions from aqueous solutions on modified sorbents - Shachneva, Evgeniya; Archibasova, Darya (Lviv Politechnic Publishing House, 2018)
Одержано нові модифіковані сорбенти на основі опок Астраханської області. Проведено порівняння сорбції кадмію на вказаних сорбентах. Вивчено ізотерми статичної сорбції речовин з водних розчинів, розраховані зміни ентальпії, ізобарно-ізотермічного потенціалу та ентропії сорбції. Розрахована кінетика сорбції йонів кадмію з водних розчинів. Показано, що результати досліджень можуть бути використані для очищення води від йонів кадмію.

Some new modified sorbents based on opoka from Astrakhan region were obtained. A comparative study of the sorption of cadmium ions on the surfaces of the sorbents was made. Also the static adsorption isotherm of substances from aqueous solutions was studied. The change of enthalpy, isobaric-isothermal potential and entropy of sorption and kinetics of cadmium ions sorption from water solutions were calculated. The results of the study can be used for the water purification from cadmium ions.
Адсорбція кадмію з водних розчинів намодифікованих сорбентах
Keywords: сорбент; сорбція; флокулянти; важкі токсичні елементи; кадмій; очищення води; sorbent; sorption; flocculants; heavy toxic elements; cadmium; water purification